From Teachers to Students - Rintamäki, Katri Maria (Qualitative and Quantitative Methods in Libraries; Vol 8 No 4 (2019): December 2019 Issue, 2019)
Literacies in their many forms are essential skills for higher education students both in their academic studies, in their future working life, and as the citizens of a highly digitalized information society in general. Information literacy education for students is an established task of academic libraries. Information literacy is taught above all for undergraduate students, but also for graduate students and even, albeit more rarely, for post doc researchers and faculty. The most significant weakness of information literacy education offered by libraries is probably, in terms of effectivity, that students perceive information literacy education as something separate from their “actual” studies and are not able to transfer the learned information skills to their subject studies. This occurs in spite of the persistent efforts of liaison librarians to adapt their information literacy teaching to the needs of each discipline. Instead, university teachers are in a key position to contribute to students’ information skills by including information practices in their teaching and tutoring. Therefore, information literacy training for university teachers is a valuable means to develop also their students’ information skills. This paper tells about practices utilized and experiences gained on piloting a digital literacy course for university teachers. Tritonia Academic Library in Vaasa, Finland was responsible for planning and teaching of the course Digital literacy and information resources , 5 ECTS. The course was a part of a 60 ECTS higher pedagogy study module that is developed and piloted in a research based and research supported development project HELLA – Higher Education Learning Lab led by Åbo Akademi University in 2017–2019. The pilot course of Digital literacy and information resources was designed in the academic year 2017–2018 and piloted in the winter 2019. In this paper, the teaching design process, learning objectives, teaching methods, and practical execution of the course are described and self-evaluated. Special attention is paid to the leaning assignments of the course in order to give some practical examples of good practices found and problems met. A special characteristic of the course design examined is its multilingualism: the course was executed in three languages, with Finnish-, Swedish- and English-speaking participants taking part in the same trilingual online course. The main forum for the teaching and learning in the course was the learning environment Moodle. All course materials, assignments, instructions, and discussions were carried out in Moodle. In addition to online studies, the course included lectures and seminar sessions arranged as hybrid teaching. Thus, lectures and seminars could be attended in the classroom or online via a videoconferencing platform. Special attention was paid to online communication, because the whole course could be completed by distance learning. In the course, different digital tools, assignment types, and teaching methods were utilized in order to give participants examples of different opportunities in besides information retrieval, also in digital teaching. To have a digital literacy course included in a higher education pedagogy study module highlighted the relevance of information literacy in teaching and research. Further research based on participants’ feedback and also long-term feedback would be worth conducting.